Metabolism of the antipsychotic drug olanzapine by CYP3A43. (3rd April 2022) - Zhao, Jie; Machalz, David; Liu, Sijie; Wolf, Clemens Alexander; Wolber, Gerhard; Parr, Maria Kristina; Bureik, Matthias
Abstract: 1. Olanzapine is an atypical antipsychotic primarily used to treat schizophrenia and bipolar disorder. An intronic single nucleotide polymorphism (SNP) that highly significantly predicts increased olanzapine clearance (rs472660) was previously identified in the CYP3A43 gene, which encodes a cytochrome P450 enzyme. But until now there was no experimental evidence for the metabolism of olanzapine by the CYP3A43 enzyme. 2. In the present study we provide this evidence, together with a thorough analysis of olanzapine metabolism by all human CYP3A enzymes. We also rationalise our findings by molecular docking experiments. Moreover, we describe the activities of several CYP3A43 mutants and present the first enzymatic activity data for the CYP3A43.3 variant; with respect to prostate cancer, this polymorphic variant is associated with both increased risk and increased mortality. The catalytic properties of the wild type enzyme and the tumour mutant were analysed by molecular dynamics simulations, which fit very well with the observed experimental results. 3. Our findings suggest that the SNP rs472660 likely causes an increased CYP3A43 expression level and demonstrate that, depending on the substrate under study, the tumour mutant CYP3A43.3 can have increased activity in comparison to the wild type enzyme CYP3A43.1.